2016
DOI: 10.1152/jn.00784.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neural spike-timing patterns vary with sound shape and periodicity in three auditory cortical fields

Abstract: Lee CM, Osman AF, Volgushev M, Escabí MA, Read HL. Neural spike-timing patterns vary with sound shape and periodicity in three auditory cortical fields. J Neurophysiol 115: 1886 -1904, 2016. First published February 3, 2016 doi:10.1152/jn.00784.2015.-Mammals perceive a wide range of temporal cues in natural sounds, and the auditory cortex is essential for their detection and discrimination. The rat primary (A1), ventral (VAF), and caudal suprarhinal (cSRAF) auditory cortical fields have separate thalamocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 98 publications
(141 reference statements)
1
24
0
Order By: Relevance
“…In particular, a large positive peak is observed at approximately 10 ms followed by a large negative peak at 25-50 ms. A second large negative peak is observed around 125 ms after the "deviant" sound, and a third follows at approximately 200 ms. The temporal dynamic of the mode suggests distinct onset and terminating responses following deviant sound onset that matches well with the dynamics observed in core or primary auditory cortices in other studies [20,38,44,55]. The reader should also notice that all signs, amplitudes, and time relative to the signal onset of the deviant match well with those depicted in Fig.…”
Section: Temporal Coordinatessupporting
confidence: 87%
“…In particular, a large positive peak is observed at approximately 10 ms followed by a large negative peak at 25-50 ms. A second large negative peak is observed around 125 ms after the "deviant" sound, and a third follows at approximately 200 ms. The temporal dynamic of the mode suggests distinct onset and terminating responses following deviant sound onset that matches well with the dynamics observed in core or primary auditory cortices in other studies [20,38,44,55]. The reader should also notice that all signs, amplitudes, and time relative to the signal onset of the deviant match well with those depicted in Fig.…”
Section: Temporal Coordinatessupporting
confidence: 87%
“…The robust correlation of NREM sleep attenuation with response latency suggests that NREM sleep may exert a gradual attenuation of cortical responses, rather than imposing a discrete 'gate' at a specific brain region. As a first approximation, AC and PRC are associated with different response latency profiles (Lee et al, 2016) and differ also in their degree of response attenuation during sleep. However, a closer examination of neuronal clusters with 'atypical' latencies reveals that their attenuation during NREM sleep is better predicted by their classification to early/late-responders rather than their anatomical location ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown to contain intrinsic inhibitory mechanisms that affect information flow to the hippocampus (Decurtis and Pare, 2004;Pelletier, 2004). Perirhinal cortex is located further downstream from the suprarhinal auditory field (SRAF) (Profant et al, 2013;Lee et al, 2016). While perirhinal neurons reliably respond to sounds during wakefulness Furtak et al, 2007), separate studies during anesthesia did not reveal significant auditory responses as one moves ventrally towards rhinal fissure (Doron et al, 2002).…”
Section: Do Sounds Effectively Modulate Responses In Downstream Assocmentioning
confidence: 99%
“…The rate of rise therefore cannot be the only factor. The onset responses of cortical and subcortical neurons are very sensitive to the rate of rise of the stimulus amplitude, as observed in many studies that have varied onset duration or sound level (Hall and Feng, 1988; Phillips, 1988; Gooler and Feng, 1992; Heil, 1997a,b; Heil and Irvine, 1998; Lee et al, 2016), but onset responses are not a unique function of this rate. Based on the effects of varying onset duration, onset shape, and sound level on the onset responses of cat auditory cortical neurons, Heil and colleagues suggested that the first spikes of the responsive population of neurons track the onset envelope and the initial steady-state portion of the stimulus (for review, see e.g., Heil, 2003).…”
Section: Discussionmentioning
confidence: 94%